2017
DOI: 10.1002/jobm.201700025
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Acanthamoeba castellanii belonging to the T4 genotype

Abstract: Here we describe features of apoptosis in unicellular Acanthamoeba castellanii belonging to the T4 genotype. When exposed to apoptosis-inducing compounds such as doxorubicin, A. castellanii trophozoites exhibited cell shrinkage and membrane blebbing as observed microscopically, DNA fragmentation using agarose gel electrophoresis, and phosphatidylserine (PS) externalization using annexin V immunostaining. Overall, these findings suggest the existence of apoptosis in A. castellanii possibly mediated by intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…16 The latter stage involves the death of corneal cells and corneal nerves 93 due to the activation of the caspases-3 and -10 dependent apoptosis cascade. 10,96 Absence of trophozoites in the anterior chamber is connected to a robust neutrophil response. 65 In some cases, the protozoan destroys all layers of corneal tissue and can lead to perforation.…”
Section: Pathogenesis Of Akmentioning
confidence: 99%
“…16 The latter stage involves the death of corneal cells and corneal nerves 93 due to the activation of the caspases-3 and -10 dependent apoptosis cascade. 10,96 Absence of trophozoites in the anterior chamber is connected to a robust neutrophil response. 65 In some cases, the protozoan destroys all layers of corneal tissue and can lead to perforation.…”
Section: Pathogenesis Of Akmentioning
confidence: 99%
“…It has been shown that mesoporous silica NPs can efficiently load and seal several therapeutic agents including doxorubicin (Wu et al 2019). Doxorubicin has been shown to cause cell death by apoptosis in amoebae (Baig et al 2017), indicating that mesoporous silica NPs show potential as nanovehicles for treatment of amoebic infections.…”
Section: Inorganic and Metallic Npsmentioning
confidence: 99%
“…Moreover, it also inhibited encystation and excystation . Apoptosis inducing drugs and compounds such as doxorubicin, caffeine, α-bisabolol, and oleic acid also hold promise for future repurposing of potential drugs and lead compounds against brain eating amoebae. More recently, clinically approved antifungal drugs including amphotericin B, nystatin, and fluconazole (all three drugs are inhibitors of ergosterol biosynthesis) were tested against A. castellanii and N. fowleri with and without conjugation with silver nanoparticles.…”
Section: Future Candidates For Drug Repurposing Against Brain-eating ...mentioning
confidence: 99%